Computational study of greenhouse gas adsorption on biochar - Khodonovych, Ivan (Jihočeská univerzita, 2020)
The thesis is focused on the adsorption mechanism of greenhouse gas such as N2O, CH4, and CO2 at the surface of biochar by classical molecular dynamics (MD) simulations. For each gas, adsorption efficiency, molecules capturing by biochar were studied at an equal range of concentrations for each gas.
Computational study of greenhouse gas adsorption on biochar
Keywords: Biochar; low-cost adsorbent; CO2; N2O; CH4; surface adsorption; gas capture; greenhouse gas; Biochar; low-cost adsorbent; CO2; N2O; CH4; surface adsorption; gas capture; greenhouse gas